Gender, Power, and Religiosity in Brazil: Approximations and Contrasts between Pentecostalism and Afro-Brazilian Religions: Gender, Power, and Religiosity in Brazil: Approximations and Contrasts between Pentecostalism and Afro-Brazilian Religions (Revista de História da UEG (REVHIST), 2025)
This article analyzes gender relations within two major religious fields in contemporary Brazilian society: Pentecostalism and Afro-Brazilian religions, with particular emphasis on Umbanda and Candomblé. From a historical-social perspective grounded in gender studies, the research investigates how these religious traditions construct, legitimize, and organize masculine and feminine roles, as well as forms of authority, leadership, and participation of women and men within their institutional and symbolic structures. The main hypothesis advanced is that, while Afro-Brazilian religions display a historical trajectory marked by female protagonism and greater flexibility in gender hierarchies, the pentecostal field tends to reproduce patriarchal models, despite undergoing transformations resulting from the increasing presence of women in its practices and discourses. In this sense, the article seeks to contribute to the understanding of the interfaces between religion and gender in Brazil, highlighting tensions, continuities, and specificities among different religious traditions.Keywords: Gender. Power. Afro-Brazilian Religiosities. Neopentecostal Religions.